Предмет: Математика,
автор: котобус
4(5-х)-3(2х+7)=0 решить уравнение
Ответы
Автор ответа:
0
20-4х-6х-21=0
-10х=1
10х=-1
-1/10=х
Х=-0,1
-10х=1
10х=-1
-1/10=х
Х=-0,1
Автор ответа:
0
4(5-х)-3(2х+7)=0
(20 - 4х) - (6х + 21) = 0
20 - 4х = 6х + 21
-4х - 6х = 21 - 20
-10х = 1
х = -0,1
(20 - 4х) - (6х + 21) = 0
20 - 4х = 6х + 21
-4х - 6х = 21 - 20
-10х = 1
х = -0,1
Похожие вопросы
Предмет: Алгебра,
автор: sweev2005
Предмет: География,
автор: spalamar27
Предмет: География,
автор: ddhdhdhdhdhjdjdjd
Предмет: Математика,
автор: Chaldonnm